Обґрунтування швидкісних параметрів роботи машинно-тракторного агрегату - Журавель, Дмитро Павлович; Журавель, Дмитрий Павлович; Zhuravel, Dmytro; Бондар, Андрій Миколайович; Бондарь, Андрей Николаевич; Bondar, Andrii; Дашивець, Галина Іванівна; Дашивец, Галина Ивановна; Dashyvets, Halyna; Паніна, Валерія Валеріївна; Панина, Валерия Валерьевна; Panina, Valeriia (My University, 2021)
UK: У статті обґрунтовано швидкісні параметри машинно-тракторного агрегату (МТА) під час виконання технологічних операцій. Розглянуто найбільш поширені сільськогосподарські операції, які потребують підвищеної точності виконання. Розроблена схема руху МТА вздовж базової лінії, яка дала змогу розробити математичну модель руху транспортного засобу з традиційним та адаптивним рульовим керуванням. Проведені розрахунки руху МТА у віртуальному режимі: з використанням ЕОМ та польові випробування. Випробування МТА проводилися на різних швидкісних режимах (зміна відбувалося від 1м/с до 3,6 м/с) під час виконання другої міжрядної обробки кукурудзи. Отримані результати підтверджують ефективність використання адаптивного рульового керування на підвищених швидкісних режимах. EN: The article analyzes the state and perspective directions of development of steering wheel tractors and determines the factors that affect the control process of the machine-tractor unit (MTA) during the transport mode and when performing technological operations. The most common agricultural operations requiring increased accuracy are considered. Particular attention is paid to inter-row cultivation of row crops, as they require increased precision. On the example, of the second inter-row processing of corn. A new method of vehicle control has been developed, which ensures the adaptability of the steering gear ratio depending on the speed of movement. A kinematic diagram of the MTA movement along the baseline has been developed, which made it possible to develop a mathematical model of vehicle movement, both with traditional and adaptive steering. A mathematical model of the MTA movement in the longitudinal plane with a new method of steering has been investigated. Comparative tests of the stability of the movement of the MTA in virtual mode and field tests were carried out. The study in virtual mode was carried out using a computer and the corresponding programs built into it. At the same time, the program allows obtaining data with a time quantization of 0.05 s, which is significantly less than the operator's response time to external disturbances. Virtual and field tests of the MTA were carried out at different speed modes - the change occurred from 1 m / s to 3.6 m / s when performing the second inter-row corn cultivation. The results obtained confirmed the effectiveness of the use of adaptive steering at high speed modes in accordance with agro technical requirements. The results obtained confirm the effectiveness of the use of adaptive steering at high speed modes. RU: В статье исследовано движение машинно-тракторного агрегата (МТА) при выполнении технологических операций и влияние возмущающих факторов, влияющих на параметры его движения. Рассмотрены наиболее распространенные сельскохозяйственные операции, требующие повышенной точности выполнения. Разработана схема движения МТА вдоль базовой линии, позволяющая разработать математическую модель движения транспортного средства с традиционным и адаптивным рулевым управлением. Произведены расчеты движения МТА в виртуальном режиме: с использованием ЭВМ и полевые испытания. Испытания МТА проводились на разных скоростных режимах (изменение происходило от 1м/с до 3,6 м/с) при выполнении второй междурядной обработки кукурузы. Полученные результаты подтверждают эффективность использования адаптивного рулевого управления на повышенных скоростных режимах.
Justification of high-speed parameters of machine-tractor unit operation
Обоснование скоростных параметров работы машинно-тракторного агрегата
Keywords: рульове керування; маневреність; траєкторія руху; базова лінія; міжрядний обробіток; агротехнічні вимоги; steering; maneuverability; trajectory of movement; baseline; inter-row processing; agro technical requirements; рулевое управление; маневренность; траектория движения; базовая линия; междурядная обработка; агротехнические требования